The use of information communication technologies in oral production courses - Sattarova Saodat Narzullayevna; Ilxomjonova Gulxayo Rustamjon qizi (Zien Journals, 2021)
In the research project, the researcher tried to identify the role of control in the development of primary education in some selected schools in the Sokoto metropolis. A simple and sampling technique research project was adopted in the study. This tool was a questionnaire for leaders and teachers in the study area to get answers on the topic. Responses from the researchers show that one of the important aspects observed in the study is that managers should not be paid if they are encouraged to perform their duties effectively. Researchers are therefore proposing that the Ministry of Education should provide in-service training and retraining for school leaders to keep them relevant in carrying out their responsibilities in their field.
Keywords: educational system; improvement; effective supervision; ICT